Archetypes of Climate Vulnerability: a Mixed-method Approach Applied in the Peruvian Andes. (28th May 2019) - Vidal Merino, Mariana; Sietz, Diana; Jost, Francois; Berger, Uta
Abstract : Farm household systems (FHSs) in the Andes handle climate-related hazards such as frost and droughts with risk-coping and risk-management strategies based on the adaptive capital available to them. Nevertheless, a higher frequency of climatic stressors observed during the last few decades is challenging their capacity to adapt at a pace fast enough to keep up with the changes in external conditions. This increases the demand on the scientific community from policy and decision makers to investigate climate impacts and propose viable adaptation pathways at the local and regional scales. Better understanding heterogeneity in climate vulnerability is an important step towards addressing this demand. We present here a mixed-method approach to assessing archetypes or patterns of climate vulnerability that combines qualitative tools from participatory rural assessment approaches and quantitative techniques including cluster analysis. We illustrate this by looking at a case study of the Central Andes of Peru. The operationalization of the methods revealed differential factors for climate vulnerability, allowing us to categorize FHS archetypes according to the differences in those underlying factors. The archetypes differed mainly according to farm area, agro-ecological zones, irrigation, off-farm employment and climate-related damages. The results suggest that the approach is useful for explaining vulnerability as a function of recurrent internal and external determinants of vulnerability and developing related adaptive strategies.